2007
DOI: 10.1213/01.ane.0000253588.61753.6b
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-Assisted Intubation: An Approach to Airway Management

Abstract: REFERENCES1. Trapnell BC, Whitsett JA, Nakata K. Pulmonary alveolar proteinosis. N Engl J Med 2003;349:2527-39. 2. Shah PL, Hansell D, Lawson PR, et al. Pulmonary alveolar proteinosis: clinical aspects and current concepts on pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 3 4 10 11 ] Prior studies have demonstrated improved glottic visualisation with their use. [ 12 13 ] However, their performance has never been evaluated in comparison with commercially available videolaryngoscopes in a difficult airway scenario.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 10 11 ] Prior studies have demonstrated improved glottic visualisation with their use. [ 12 13 ] However, their performance has never been evaluated in comparison with commercially available videolaryngoscopes in a difficult airway scenario.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Laparoscopes are now freely available in most setups without the additional cost of a videolaryngoscope designed to tackle difficult airway, to provide a clear anatomical view of the glottic area, to be able to ‘look around the corner’,[3] and to view the glottis via the camera without aligning the oral, pharyngeal and laryngeal axes. Therefore, a potential C and L grade III or IV glottic view should become a C and L grade I or II view with laparoscopic assistance.…”
Section: Discussionmentioning
confidence: 99%